Konfrontativer Vergleich der Nomina agentis im Deutschen und Polnischen - Storczyk, Irena (Studia Germanica Posnaniensia, 2018)
The article is an attempt at the description of formations, known in linguistics as nomina agentis (names of the actor), comparisons of structural types, occurring in German and Polish, and at showing both similarities and differences between them, and their participation in the construction of formation of the typical word-formational morphemes.